2003
DOI: 10.1590/s0021-75572003000600015
|View full text |Cite
|
Sign up to set email alerts
|

Fatores maternos e neonatais na incidência de displasia broncopulmonar em recém-nascidos de muito baixo peso

Abstract: Gestational age and birthweight were inversely proportional to incidence of bronchopulmonary dysplasia. After the onset of bronchopulmonary dysplasia, newborns with the disorder required longer periods of ventilator therapy and hospitalization, and presented inadequate weight gain and higher mortality rates than newborns without bronchopulmonary dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
2
13
0
13
Order By: Relevance
“…95 ISSN 2317-2460 -doi: http://dx.doi.org/10.18616/is.v4i2.2238. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] articles were used from 2000 to 2016. Discussion: Bronchopulmonary dysplasia is a multifactorial disease.…”
Section: Artigo De Revisão Fisiopatologiamentioning
confidence: 99%
See 3 more Smart Citations
“…95 ISSN 2317-2460 -doi: http://dx.doi.org/10.18616/is.v4i2.2238. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] articles were used from 2000 to 2016. Discussion: Bronchopulmonary dysplasia is a multifactorial disease.…”
Section: Artigo De Revisão Fisiopatologiamentioning
confidence: 99%
“…A displasia broncopulmonar é uma doença multifatorial, que vai desde a intoxicação por frações inspiradas de oxigênio elevadas e uso de ventilação mecânica invasiva por longos períodos de tempo a doenças pré-existentes, como persistência do canal arterial, síndrome das membranas hialinas (síndrome do desconforto respiratório do recém-nascido), infecções neonatais e outras doenças 1,2,3,4,5,6,7,8 .…”
Section: Fisiopatologiaunclassified
See 2 more Smart Citations
“…Furthermore, case descriptions vary substantially from one health center to another, due to the different populations analyzed, to the lack of standardized ventilatory strategies for the treatment of acute lung disease, to the great variability regarding fluid administration and the care of critically ill newborns and to the different diagnostic criteria used to define the disease (Table 2). [9][10][11][12] In Brazil, Cunha et al 13 found a DBP incidence of 26.6% during evaluation of 124 infants with birth weights under 1,500 g who survived more than 28 days during years 2000 and 2002.…”
Section: Incidencementioning
confidence: 99%